Nutritional interventions to support acute mTBI recovery - Finnegan, Emma; Daly, Ed; Pearce, Alan J.; Ryan, Lisa (Frontiers in Nutrition, 2022)
When mild traumatic brain injury (mTBI) occurs following an impact on the head or body, the brain is disrupted leading to a series of metabolic events that may alter the brain's ability to function and repair itself. These changes may place increased nutritional demands on the body. Little is known on whether nutritional interventions are safe for patients to implement post mTBI and whether they may improve recovery outcomes. To address this knowledge gap, we conducted a systematic review to determine what nutritional interventions have been prescribed to humans diagnosed with mTBI during its acute period (<14 days) to support, facilitate, and result in measured recovery outcomes. Methods Databases CINAHL, PubMed, SPORTDiscus, Web of Science, and the Cochrane Library were searched from inception until January 6, 2021; 4,848 studies were identified. After removing duplicates and applying the inclusion and exclusion criteria, this systematic review included 11 full papers. Results Patients that consumed enough food to meet calorie and macronutrient (protein) needs specific to their injury severity and sex within 96 h post mTBI had a reduced length of stay in hospital. In addition, patients receiving nutrients and non-nutrient support within 24–96 h post mTBI had positive recovery outcomes. These interventions included omega-3 fatty acids (DHA and EPA), vitamin D, mineral magnesium oxide, amino acid derivative N-acetyl cysteine, hyperosmolar sodium lactate, and nootropic cerebrolysin demonstrated positive recovery outcomes, such as symptom resolution, improved cognitive function, and replenished nutrient deficiencies (vitamin D) for patients post mTBI. Conclusion Our findings suggest that nutrition plays a positive role during acute mTBI recovery. Following mTBI, patient needs are unique, and this review presents the potential for certain nutritional therapies to support the brain in recovery, specifically omega-3 fatty acids. However, due to the heterogenicity nature of the studies available at present, it is not possible to make definitive recommendations. Systematic review registration The systematic review conducted following the PRISMA guidelines protocol was registered (CRD42021226819), on Prospero.